Chronic Exertional Compartment Syndrome in a High School Soccer Player - James J. Bresnahan; William L. Hennrikus (Case Reports in Orthopedics)
Chronic exertional compartment syndrome (CECS) is a relatively rare condition that affects young adult athletes and often causes them to present to the emergency department. If left untreated, those who continue to compete at high levels may experience debilitating leg pain. Physicians may have difficulty differentiating CECS from other syndromes of the lower leg such as medial tibial stress syndrome, stress fractures, and popliteal artery entrapment. The gold standard for diagnosing CECS is intramuscular compartment pressure monitoring before and/or after 10 minutes of exercise. Some patients may choose to stop participation in sports in order to relieve their pain, which otherwise does not respond well to nonoperative treatments. In patients who wish to continue to participate in sports and live an active life, fasciotomy provides relief in 80% or more. The typical athlete can return to training in about 8 weeks. This is a case of a high school soccer player who stopped competing due to chronic exertional compartment syndrome. She had a fascial hernia, resting intramuscular pressure of 30 mmHg, and postexercise intramuscular pressure of 99 mmHg. Following fasciotomy she experienced considerable life improvement and is once again training and playing soccer without symptoms.